Review: What innovations in pain measurement and control might be possible if we could quantify the neuroimmune synapse?. (13th August 2019) - Hutchinson, M. R.; Terry, R.
Abstract : It has taken more than 40 years for the fields of immunology and neuroscience to capture the potential impact of the mechanistic understanding of how an active immune signalling brain might function. These developments have grown an appreciation for the immunocompetent cells of the central nervous system and their key role in the health and disease of the brain and spinal cord. Moreover, the understanding of the bidirectional communication between the brain and the peripheral immune system has evolved to capture an understanding of how mood can alter immune function and vice versa . These concepts are rapidly evolving the field of psychiatry and medicine as a whole. However, the advances in human medicine have not been capitalised upon yet in animal husbandry practice. Of specific attention are the implications that these biological systems have for creating and maintaining heightened pain states. This review will outline the key concepts of brain–immune communication and the immediate opportunities targeting this biology can have for husbandry practices, with a specific focus on pain.